Colonialismo, instrumentalização da pobreza e mercantilização dos recursos naturais da Amazônia - Carletti, Rafael (Universidade Federal de São Carlos, 2023)
This thesis seeks to discuss how the discourse on global warming and climate change reproduces colonialist ideas about the people and nature of the Amazon. Still, it seeks to understand how these ideas are discursively mobilized, in the sense of subsidizing the implementation of environmental public policies. Therefore, two analytical references are used to examine this problem. The first concerns the process of colonization and colonialism, as they are fundamental aspects of the socio-historical construction of both the peoples and the nature of the Amazon. The second refers to the institutionalization of the so-called social and environmental issues which, as they were consolidated within the framework of Modernity, made the process of social formation of peoples and social construction of nature invisible. Thus, the work's hypothesis is that the notions of traditional peoples and of an exotic nature – both formulated in the colonial period – are the main ones to be mobilized by environmentalism to legitimize environmental public policies in the region. Theoretically, the thesis is based on the idea of caboclo societies as a way of dialoguing with the category of traditional peoples. In addition, it mobilizes references from ecological economics, environmental economics and the Marxist critique of political economy, to discuss the idea of nature. The methodological resources used were bibliographic references, document analysis, interviews and participant observation. The thesis did not seek to confirm its hypothesis or draw definitive conclusions, but rather to expand the possibilities for discussion on this topic.
Colonialism, instrumentalization of poverty and commodification of the natural resources of Amazon
Keywords: Neoliberalismo; Desenvolvimento sustentável; Pagamento por Serviços Ambientais; Unidades de Conservação; Ribeirinhos; Neoliberalism; Sustainable Development; Payment for Environmental Services; Protected Areas; Riverside; CIENCIAS HUMANAS::SOCIOLOGIA